(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Employee motivation plays an important role to elevate the working of an organization. In the phase of internationalization, every organization needs to sustain in the fierce competitive market. Employees are considered to be an important factor to exhibit the organizational goals into reality. Therefore, in today’s world every business tries to manage their human resource department to keep their employees motivated. The function of an organization or their performance in the market can be evaluated by assessinghow the employees are motivated. Motivation can play an important role in achieving the goals of an organization.